RAD21 COHESIN OVEREXPRESSION IS A PROGNOSTIC AND PREDICTIVE MARKER EXACERBATING POOR PROGNOSIS IN KRAS MUTANT COLORECTAL CARCINOMAS. (February 2015) - Deb, Siddhartha; Xu, Huiling; Tuynman, Jurriaan B.; George, Joshy; Yan, Yuqian; Li, Jason; Ward, Robyn; Mortensen, Neil; Hawkins, Nicholas; McKay, Michael; Ramsay, Robert G.; Fox, Stephen B.
Abstract : Introduction: RAD21 is a component of the cohesion complex integral to chromosome segregation and error-free DNA repair. RAD21 is functionally important in tumour progression but its role in colorectal carcinoma (CRC) is unclear. Therefore, we assessed its clinicopathological and prognostic significance in CRC, as well as its effect on chemosensitivity. Methods: RAD21 expression in 652 CRCs was examined with clinicopathological and molecular correlation. Colorectal cancer cell clones with stable RAD21 knockdown were generated and tested for cellular sensitivity to conventional chemotherapeutic drugs. Results: RAD21 expression significantly correlated with male gender (56.7% vs 43.3%, p = 0.02), well-differentiated histology (14.4% vs 4.0%, p = 0.0001), higher T-stage (36.1% vs 27.0%, p = 0.01), presence of metastasis (18.8% vs 12.6%, p = 0.03), and shorter disease specific survival [hazard ratio (HR) 1.4, 95%CI 1.1–1.9, p = 0.01] in univariate and multivariate analysis. RAD21 expression was associated with shorter DSS when tumours harboured a KRAS mutation (HR 2.6, 95%CI 1.4–4.3, p = 0.001) and in patients receiving adjuvant chemoradiotherapy (HR 1.9, 95%CI 1.2–3.0, p = 0.008). Colorectal cancer cells with RAD21 knockdown exhibited enhanced sensitivity to 5-fluorouracil. Conclusions: RAD21 expression in CRC is associated with aggressive disease especially in KRAS mutant tumours and resistance to chemoradiotherapy. RAD21 may be an important novel therapeutic target.